Can workplace inducements influence labour turnover? - Agba, A.M. Ogaboh; Angioha, Pius U.; Akpabio, Ntiense G.; Akintola, Abayomi; Maruf, Gbadebo S. (Yayasan Ahmar Cendekia Indonesia, 2021)
The study examines workplace inducements and labour turnover. Specifically, the study sought to establish the relationship between staff promotion, performance-based bonuses, employee discount, training, and labour turnover in the telecommunications industry in South-South, Nigeria. The study adopted a survey research design. Using a self-report questionnaire. Data was collected from five hundred and seventy-two (572) staff selected in four (4) telecommunications industry in South-South, Nigeria. The obtained data were statistically analysed using simple linear regression. Each hypothesis was tested at 0.05 per cent level of significance. The result obtained from the analysis revealed that staff promotion, performance-based bonuses, employee discount and training significantly affect labour turnover in the telecommunications industry in South-South, Nigeria. The study recommended among others that policy options that encourage improved incentives for employees in telecommunications Company.